2006
DOI: 10.1197/jamia.m1809
|View full text |Cite
|
Sign up to set email alerts
|

Overriding of Drug Safety Alerts in Computerized Physician Order Entry

Abstract: Many computerized physician order entry (CPOE) systems have integrated drug safety alerts. The authors reviewed the literature on physician response to drug safety alerts and interpreted the results using Reason's framework of accident causation. In total, 17 papers met the inclusion criteria. Drug safety alerts are overridden by clinicians in 49% to 96% of cases. Alert overriding may often be justified and adverse drug events due to overridden alerts are not always preventable. A distinction between appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
670
4
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 906 publications
(702 citation statements)
references
References 51 publications
18
670
4
10
Order By: Relevance
“…A recent review found that providers overrode alerts 49-96 % of the time. 25 In one study, VHA clinicians rated only 11 % of reminders as clinically relevant, and in another study, a VA researcher found that 80 % of drug interaction warnings were ignored. 26,27 Studies of CCDS tools that allow for more complex data input have shown better performance of alerts.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review found that providers overrode alerts 49-96 % of the time. 25 In one study, VHA clinicians rated only 11 % of reminders as clinically relevant, and in another study, a VA researcher found that 80 % of drug interaction warnings were ignored. 26,27 Studies of CCDS tools that allow for more complex data input have shown better performance of alerts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the value of CDS is often limited by providers' lack of alert acceptance. Multiple studies have shown that providers frequently override alerts because they are perceived as irrelevant [39][40][41][42] . The inability of EHR systems to effectively present information for CDS purposes may contribute to the mixed safety benefits observed in studies 1,[7][8][9][10]12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…What accounts for this seemingly paradoxical result? With a positive predictive value of only 2.3% and 41,922 alerts, physicians may have become desensitized to alerted patients due to alert fatigue [22]. Modifications of the CDSS are planned to decrease the number of alerts and improve the specificity of the program.…”
Section: Discussionmentioning
confidence: 99%